The Three Most Critical Aspects for Implementing Holistic Customer Experience at Scale - Shashank Katare (Global Journal of Management and Business Research, 2023)
Businesses are increasingly challenged by increasing competition changing customer preferences and industry dynamics Moreover proliferation of channels and customer touchpoints have added to the complexity of keeping up with these constant changes Only organizations who are nimble enough to understand evaluate and react to these dynamic requirements can drive innovation and growth This means organizations must be creative in their consumer engagement strategies across the marketing funnel to enhance overall customer experience measure the performance and establish the loopback to constantly refine the strategies The following paper outlines concepts to help consumer businesses accelerate customer experience management The objective of the paper is to lay out guiding principles that organizations can use as part of their business processes to create deliver and measure personalized customer experiences that will drive growth loyalty and satisfaction